Understanding Indonesian Vocational High School Students’ Process of Learning: A Case Study on Chemical Analysis Vocational High School in Pontianak - Yulistiani, Ribka; Kurniawan, Rizmahardian Ashari; Kurniati, Tuti; Mukhlishin, Hamdil (PENA KREATIF : JURNAL PENDIDIKAN, 2024)
This research is a descriptive study that generally aims to analyze the results of chemistry learning in the acid-base subject of class XI 4 students at SMKN 4 Pontianak in terms of their learning styles. Students at SMKN 4 Pontianak have varied learning outcomes and different learning methods and styles. Learning styles are very important to know for both teachers and students of class XI APL SMKN 4 Pontianak. With knowledge of learning styles, we can identify and use learning methods that best suit each student's learning preferences. This can result in a better and more effective understanding of the material, as well as increasing satisfaction in the learning process. The instruments for this research are a learning style questionnaire, interview guide. Based on the results of data analysis, information was obtained that the tendency for student learning styles to be dominated by the kinesthetic learning style for unimodal learning styles was 56.25% and the K-V learning style for multimodal learning styles was 18.75%. The students' learning outcomes on the acid-base material taught by the teacher show the following daily average scores: acid-base titration 70.3, Mohr titration 73.9, and redox titration 76.4.